ANALISIS DAMPAK KEBIJAKAN MONETER TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2015-2024 - Fahmi Aminullah; Alimin Alimin; Lili Ramahdani (AL-ITTIFAQ Jurnal Ekonomi Syariah, 2025)
The purpose of this study is to analyze the effect of monetary policy on Indonesia’s economic growth in the period of 2015–2024 using the interest rate of the Indonesian Bank Certificate Sertifikat Bank Indonesia, the money supply, the exchange rate, and inflationary pressure as the independent variable, and the economic growth as the dependent variable. The study used the quantitative research method by taking secondary data from the Central Bureau of Statistics and the Bank of Indonesia then analyzed using multiple linear regression with the Ordinary Least Squares method which is supplemented by t test, F test, coefficient of determinant R², and classic assumption test to ensure if the model is valid. The research findings showed that the SBI interest rate has a negative and significant influence on economic growth, inflation has a positive and significant effect, and the money supply and the exchange rate do not have a significant influence. Simultaneously, all four independent variables have a significant impact on economic growth by a value of R² of 73.35%. It means most of the variation of economic growth can be explained by independent variable of this model, while the rest is influenced by other factors beyond this research. In conclusion, the research finding asserted that monetary policy has an important role in maintaining stability and promoting economic growth in Indonesia, especially with main contribution as a recommendation for policymakers and monetary authorities to control interest rate and inflation and to recommend for further research by adding more variable such as investment, export, import, and government expenditure.